Measuring The Impact Of Trust On Job Performance And Self-Efficacy In A Project: Evidence From Saudi Arabia - Varshney, Deepanjana; Varshney, Nirbhay K. (Journal of Applied Business Research, 2017)
The individual’s ability to complete the given task effectively can be termed as Self-efficacy. Employee performance is examined about outcomes and behavior. Job performance determines the quality as well as the quantity accomplished by employees over a period. Trust has been widely used as a mediating variable in previous research and has been found to exhibit positive mediating effects on the variables.In our research, we have investigated the factors (Team-self-efficacy and trust) affecting the project team members’ job performance. We have conducted a study to collect data and test the model proposed on 155 respondents (project team members) of a large construction company at Saudi Arabia. The findings demonstrated that trust partially mediated the relationship between the team job performance and self-efficacy. Additionally, significant positive correlations between the variables were found. There have been several studies examining the variables as discussed in the paper. However, there is a paucity of research on small groups like the project teams worldwide. The significance of the results and future research directions were analyzed and discussed. The importance of the results and directions for future research were also put forward.
Keywords: Job Performance; Project Team; Saudi Arabia; Team Self-Efficacy; Trust